2015
DOI: 10.5812/aapm.22846
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Administration of Active Recombinant Factor VII on Postoperative Bleeding in Cardiac Valve Reoperations; A Randomized Clinical Trial

Abstract: Background:Postoperative bleeding after cardiac reoperations is among the most complicating problems, both for the physicians and for the patients. Many modalities have been used to decrease its adverse effects and the need for blood products administration.Objectives:In a randomized double-blinded clinical trial of redo cardiac valve surgery in adult, the effect of active recombinant factor VII (rFVIIa) on postoperative bleeding was compared with placebo. Chest tube drainage was used for comparison of bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Payani et al . [ 20 ] in a randomized clinical trial studied the effect of prophylactic use of low dose 40 mcg/kg rFVII on patients undergoing redo valve surgeries. They concluded that 40 mcg/kg of rFVII could be effective in reducing the volume of postoperative chest tube drainage and need for blood transfusion, with no thromboembolic event.…”
Section: Discussionmentioning
confidence: 99%
“…Payani et al . [ 20 ] in a randomized clinical trial studied the effect of prophylactic use of low dose 40 mcg/kg rFVII on patients undergoing redo valve surgeries. They concluded that 40 mcg/kg of rFVII could be effective in reducing the volume of postoperative chest tube drainage and need for blood transfusion, with no thromboembolic event.…”
Section: Discussionmentioning
confidence: 99%
“…For both groups, the coronary artery bypass was performed in the culprit lesions by a surgical team. All patients were treated according to a fixed protocol for general anesthesia, surgical, hemodynamic, and CPB management, which has already been described in detail [18]. Mean arterial pressure was maintained on 60–80 mm Hg, and deviations were corrected with nitroglycerin and phenylephrine (after optimization of preload, CVP ≥10 cm H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, only 4 of the 29 studies involved cardiac surgical patients (four of the five randomized adult cardiac surgical studies were cited 35,36,38,39 ; the fifth was yet to be published). 37 Despite this small subset of cardiac surgical patients, the authors still advised that the “effectiveness of recombinant activated factor VII as a more general hemostatic drug, either prophylactically or therapeutically, remains unproven. The use recombinant activated factor VII outside its current licensed indications should be restricted to clinical trials.”…”
Section: Meta-analyses Of Unlicensed Recombinant Activated Factor Vii...mentioning
confidence: 99%